Low-alloy high-toughness zirconium alloy and preparation method thereof
By adding titanium, niobium and hafnium elements to the metal zirconium and adopting low alloying modification and heat treatment processes, the problem of insufficient biocompatibility and yield strength in orthopedic implantation of zirconium alloys is solved, and a zirconium alloy material with high strength and toughness and low elastic modulus is achieved.
Patent Information
- Application Number
- CN202411961691.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
The existing alloy materials used for orthopedic implantation have biocompatibility problems caused by mismatch of human bone elastic modulus and release of harmful metal ions in service. At the same time, their yield strength is low, which limits its wide application.
By adding titanium, niobium and hafnium elements to the metal zirconium, the strength of the zirconium alloy is increased by solid solution strengthening method, and its mechanical properties are optimized through low alloying modification and heat treatment processes.
The high yield strength (620-675MPa) and low elastic modulus (85±2GPa) of zirconium alloy are achieved, suitable for use as hard tissue implant materials, and improve its stability and biocompatibility in the human body.
Smart Images

Figure CN119753394A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloy materials, and in particular to a low-alloy high-strength and toughness zirconium alloy and a preparation method thereof. Background Art
[0002] Against the backdrop of rapid development of modern industry and technology, the demand for high-performance alloy materials in human production and life has become increasingly urgent, and the research and development of titanium-zirconium-niobium alloys has emerged as the times require. The alloys currently used in clinical orthopedic implants have biocompatibility issues caused by the mismatch between the elastic modulus of human bones and the release of harmful metal ions. In order to meet the needs of the orthopedic implant field, the third-generation metastable β-type titanium alloys with low elastic modulus and good biocompatibility have been rapidly developed, but the low yield strength (≤600Mpa) of this type of alloy limits its widespread application. Therefore, it is urgent to develop medical metal implant materials with both low elastic modulus and high yield strength.
[0003] Zirconium has better corrosion resistance, better biocompatibility, and extremely low magnetic susceptibility (which can avoid a large number of nuclear magnetic imaging artifacts that affect the repair and renovation of implants) than titanium, and has great application potential in the field of medical implants. However, the strength of pure zirconium is low, and in long-term use, it may cause deformation or even cracking, leading to implant failure. Therefore, improving the strength of zirconium is a key issue in expanding its application range. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a low-alloy high-strength and high-toughness zirconium alloy having both high strength and toughness and low elastic modulus and a preparation method thereof.
[0005] In the technical solution of the present invention, low alloying is a conventional material modification method in the art, which improves the performance by adding a small amount of alloying elements (the addition amount of each alloying element is ≤5%) to the base metal.
[0006] To achieve the above object, the technical solution adopted by the present invention is:
[0007] In one aspect, the present invention provides a method for preparing a low-alloy high-strength and tough zirconium alloy, comprising the following steps:
[0008] Step (1) alloy smelting;
[0009] Step (2) alloy homogenization;
[0010] Step (3) hot rolling treatment: the temperature of the hot rolling treatment is 880-920° C.; the reduction rate of the hot rolling treatment is 80%-85%;
[0011] Step (4) annealing;
[0012] Wherein, the alloy elements added to the low-alloy high-strength and toughness zirconium alloy include titanium, niobium and hafnium.
[0013] As a preferred embodiment, the chemical composition of the low-alloy high-strength and toughness zirconium alloy includes, by mass percentage: titanium: 4.8% to 5.0%; niobium: 0.5% to 5.0%; hafnium: 1.5% to 3.0%; the remainder being zirconium and unavoidable impurity elements.
[0014] In certain specific embodiments, step (1) uses a water-cooled copper crucible non-consumable vacuum arc furnace to melt the alloy; the alloy smelting is carried out in an inert atmosphere; to ensure the uniformity of the alloy ingot obtained by smelting, the smelting is repeated 6 to 8 times, and magnetic stirring is turned on to assist homogenization; after the alloy smelting is completed, it is cooled by circulating cooling water.
[0015] As a preferred embodiment, in step (2), the temperature of the alloy homogenization is 880-920°C;
[0016] Preferably, the alloy homogenization time is 8 to 10 hours;
[0017] Preferably, the heating rate of the alloy homogenization is 10-15°C / min;
[0018] Preferably, the alloy further comprises a water cooling quenching step after homogenization;
[0019] Preferably, the alloy homogenization is performed in an inert atmosphere.
[0020] As a preferred embodiment, in step (3), the hot rolling process is performed for 8 to 10 passes; the reduction rate of a single pass is 8% to 10%;
[0021] Preferably, a heat preservation treatment is performed before each rolling in the hot rolling process;
[0022] Preferably, the temperature of the heat preservation treatment is the same as the temperature of the hot rolling treatment;
[0023] Preferably, in the hot rolling process, the holding time before the first rolling is 25 to 35 minutes; the holding time before the remaining rolling is 2 to 4 minutes; in the technical solution of the present invention, the holding treatment for 25 to 35 minutes before the first rolling can prevent the alloy from cracking during rolling at low temperature, and is also conducive to obtaining a precise hot rolling temperature;
[0024] Preferably, the hot rolling process further includes a water cooling operation.
[0025] As a preferred embodiment, in step (4), the annealing temperature is 650-750°C;
[0026] Preferably, the annealing time is 10 to 15 minutes;
[0027] In some specific embodiments, the annealing further includes a cooling operation; the cooling is furnace cooling to 250-350° C. and then air cooling.
[0028] In another aspect, the present invention provides a low-alloy high-strength and toughness zirconium alloy obtained by the above preparation method.
[0029] The present invention has the following advantages and beneficial effects:
[0030] The present invention adds titanium, niobium and hafnium elements to metal zirconium to increase the strength of metal zirconium through solid solution strengthening. At the same time, in order to avoid the pitting of metal zirconium that may be caused by high alloying, the present invention ensures a low addition amount of each alloy element through low alloying modification; and with the help of deformation and heat treatment processes, further optimizes its mechanical properties so that it can better withstand various stresses, thereby providing a guarantee for long-term and stable function inside the human body, and meeting the urgent demand for high-performance implant materials in the biomedical field. Compared with metal zirconium and the current medical implant zirconium-niobium alloy (yield strength 310-400MPa, elastic modulus ~95GPa), the zirconium alloy prepared by the present invention has a higher yield strength (620-675MPa) and a lower elastic modulus (85±2GPa), which is more conducive to use as a hard tissue implant material.
[0031] In addition, the preparation method provided by the present invention has simple process and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the shape and size of a sample in a tensile test experiment of a low-alloy zirconium-titanium-niobium-hafnium alloy in an embodiment of the present invention.
[0033] Figure 2 This is an XRD test diagram of the low alloy zirconium-titanium-niobium-zirconium alloy in the embodiment of the present invention.
[0034] Figure 3a to Figure 3c They are respectively the microstructure diagrams of the low alloy zirconium-titanium-niobium-zirconium alloys in Examples 1 to 3 of the present invention.
[0035] Figure 4 These are the mechanical property test results of the low alloy zirconium-titanium-niobium-zirconium alloy in the embodiments of the present invention. DETAILED DESCRIPTION
[0036] The following embodiments are only some embodiments of the present invention, rather than all embodiments. Therefore, the detailed description in the embodiments of the present invention provided below is not intended to limit the scope of the present invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the protection scope of the present invention.
[0037] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0038] Example 1
[0039] The preparation process of the low alloy zirconium-titanium-niobium-hafnium alloy in this embodiment is as follows:
[0040] Industrial pure zirconium, pure titanium and pure niobium are melted in an argon atmosphere by using a water-cooled copper crucible non-consumable vacuum arc furnace. During the melting process, the ingot is repeatedly melted for 7 times and magnetic stirring is turned on to obtain a zirconium-titanium-niobium-hafnium alloy ingot.
[0041] The alloy ingot was placed in a vacuum tube furnace and heated to 900°C at a heating rate of 15°C / min for homogenization for 10 hours, with argon gas being introduced during the homogenization process, followed by water cooling and quenching.
[0042] The muffle furnace is heated to 900°C at a heating rate of 10°C / min, and the homogenized alloy ingot is placed in the muffle furnace and kept warm for 30 minutes; immediately after the end of the heat preservation, the alloy ingot is taken out and hot rolled on a double-roll mill, the hot rolling temperature is 900°C, 10 rolling passes are adopted, and the reduction of each rolling deformation is 8.2%. After the first rolling pass, the alloy ingot is kept warm at 900°C in the muffle furnace for 5 minutes before each rolling; the final rolling deformation is about 82%; and the alloy ingot is water-cooled to room temperature;
[0043] The rolled plate was annealed at 700°C for 10 minutes in an argon atmosphere in a tubular furnace; after annealing, the furnace was cooled to 300°C and then air-cooled; finally, the surface oxide layer was polished and cleaned to obtain a low-alloy zirconium-titanium-niobium-hafnium alloy plate.
[0044] The thickness of the low-alloy zirconium-titanium-niobium-hafnium alloy plate prepared in this embodiment is 2.5 mm.
[0045] The low-alloy zirconium-titanium-niobium-hafnium alloy plate prepared in this embodiment is tested to have a composition of Zr-4.91Ti-0.94Nb-2.35Hf.
[0046] Example 2
[0047] The preparation process of the low alloy zirconium-titanium-niobium-hafnium alloy in this embodiment is as follows:
[0048] Industrial pure zirconium, pure titanium and pure niobium are melted in an argon atmosphere by using a water-cooled copper crucible non-consumable vacuum arc furnace. During the melting process, the ingot is repeatedly melted for 7 times and magnetic stirring is turned on to obtain a zirconium-titanium-niobium-hafnium alloy ingot.
[0049] The alloy ingot was placed in a vacuum tube furnace and heated to 900°C at a heating rate of 15°C / min for homogenization for 10 hours, with argon gas being introduced during the homogenization process, followed by water cooling and quenching.
[0050] The muffle furnace is heated to 900°C at a heating rate of 10°C / min, and the homogenized alloy ingot is placed in the muffle furnace and kept warm for 30 minutes; immediately after the end of the heat preservation, the alloy ingot is taken out and hot rolled on a double-roll mill, the hot rolling temperature is 900°C, 10 rolling passes are adopted, and the reduction of each rolling deformation is 8.5%. After the first rolling pass, the alloy ingot is kept warm at 900°C in the muffle furnace for 5 minutes before each rolling; the final rolling deformation is about 85%; and the alloy ingot is water-cooled to room temperature;
[0051] The rolled plate was annealed at 700°C for 10 minutes in an argon atmosphere in a tubular furnace; after annealing, the furnace was cooled to 300°C and then air-cooled; finally, the surface oxide layer was polished and cleaned to obtain a low-alloy zirconium-titanium-niobium-hafnium alloy plate.
[0052] The thickness of the low-alloy zirconium-titanium-niobium-hafnium alloy plate prepared in this embodiment is 2.5 mm.
[0053] The low-alloy zirconium-titanium-niobium-hafnium alloy plate prepared in this embodiment has a composition of Zr-4.87Ti-2.50Nb-2.21Hf after testing.
[0054] Example 3
[0055] The preparation process of the low alloy zirconium-titanium-niobium-hafnium alloy in this embodiment is as follows:
[0056] Industrial pure zirconium, pure titanium and pure niobium are melted in an argon atmosphere by using a water-cooled copper crucible non-consumable vacuum arc furnace. During the melting process, the ingot is repeatedly melted for 7 times and magnetic stirring is turned on to obtain a zirconium-titanium-niobium-hafnium alloy ingot.
[0057] The alloy ingot was placed in a vacuum tube furnace and heated to 900°C at a heating rate of 15°C / min for homogenization for 10 hours, with argon gas being introduced during the homogenization process, followed by water cooling and quenching.
[0058] The muffle furnace is heated to 900°C at a heating rate of 10°C / min, and the homogenized alloy ingot is placed in the muffle furnace for 30 minutes of heat preservation; immediately after the heat preservation, the ingot is taken out and hot rolled on a double-roll mill, the hot rolling temperature is 900°C, 10 rolling passes are adopted, and the reduction of each rolling deformation is 8.4%. After the first rolling pass, the ingot is kept at 900°C in the muffle furnace for 5 minutes before each rolling; the final rolling deformation is about 84%; and the ingot is water-cooled to room temperature;
[0059] The rolled plate was annealed at 700°C for 10 min in an argon atmosphere in a tubular furnace; after annealing, the furnace was cooled to 300°C and then air-cooled; finally, the surface oxide layer was polished and cleaned to obtain a low-alloy zirconium-titanium-niobium-hafnium alloy plate.
[0060] The thickness of the low-alloy zirconium-titanium-niobium-hafnium alloy plate prepared in this embodiment is 2.5 mm.
[0061] The low-alloy zirconium-titanium-niobium-hafnium alloy plate prepared in this embodiment has a composition of Zr-4.95Ti-4.93Nb-2.25Hf after testing.
[0062] Performance Test:
[0063] The phase composition of the low alloy zirconium-titanium-niobium-hafnium alloy sheet prepared in the above embodiment was tested by X-ray diffraction (XRD). Figure 2 ,from Figure 2 It can be seen that the addition of Nb can change the phase composition of Ti-Zr alloy, thus affecting the β-stabilizing ability of the alloy. As the Nb content increases further, the XRD results show that the alloy in Example 1 has an α phase, the alloy in Example 2 has an α phase and a β phase, and the alloy in Example 3 has an α phase, a β phase, and an ω phase. The alloy element Ti has a neutral effect on the phase stability of metal zirconium when there are no other β-stabilizing elements. When there are other β-stabilizing elements, its β-stabilizing ability increases with the increase of the content, which can improve the toughness of the material. At the same time, the ω phase can improve the strength of the material and reduce the magnetic susceptibility.
[0064] The microstructure of the low alloy zirconium-titanium-niobium alloy plate prepared in the above embodiment was observed by scanning electron microscopy (SEM), and the test results are shown in Figure 3. It can be seen from Figure 3 that the microstructure of the alloy of Example 1 is characterized by fine short rod-shaped structure (thickness less than 1 micron, length 3-5 microns) and a very small amount of intergranular β phase. The microstructure morphology characteristics of Example 2 and Example 3 are similar, that is, a typical incompletely recrystallized structure, consisting of mainly fine equiaxed crystals (size 0.5-1 micron) and a small amount of short rod-shaped grains (thickness about 0.7-1 micron, length 2-3 microns), and a large amount of β phase matrix.
[0065] The low alloy zirconium-titanium-niobium-hafnium alloy plates prepared in Examples 1 to 3 were subjected to a tensile test. The process was as follows: Figure 1 For the tensile specimens shown, at least 5 tensile specimens were cut out of each sample, and the surface was polished and smooth. The mechanical properties were tested by uniaxial tensile test at room temperature. During the test, the tensile displacement of the specimen was monitored by an extensometer. The tensile process was strain controlled, and the rate was 5×10 -4 s -1 The test results are shown in Figure 4 As shown in Table 1. Figure 4 It can be seen from Table 1 that the prepared material has the performance characteristics of higher yield strength (620-700 MPa) and lower Young's modulus (85±2 GPa).
[0066] Table 1
[0067] Elastic modulus GPa Yield strength MPa Tensile strength MPa Elongation % Example 1 83.5±0.5 623.8±10.0 737.3±7.1 11.1±1.5 Example 2 86.5±0.5 653.5±20.1 766.6±14.0 11.0±3.0 Example 3 85±2 675.1±19.0 746.1±42.1 7.3±3.2
[0068] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a low-alloy high-strength and tough zirconium alloy, characterized in that: The following steps are involved: Step (1) alloy smelting; Step (2) alloy homogenization; Step (3) hot rolling treatment: the temperature of the hot rolling treatment is 880-920° C.; the reduction rate of the hot rolling treatment is 80%-85%; Step (4) annealing; Wherein, the alloy elements added to the low-alloy high-strength and toughness zirconium alloy include titanium, niobium and hafnium.
2. The preparation method according to claim 1, characterized in that: The chemical composition of the low-alloy high-strength and toughness zirconium alloy includes, by mass percentage: titanium: 4.8% to 5.0%; niobium: 0.5% to 5.0%; hafnium: 1.5% to 3.0%; the remainder is zirconium and unavoidable impurity elements.
3. The preparation method according to claim 1, characterized in that: Step (1) uses a water-cooled copper crucible non-consumable vacuum arc furnace to melt the alloy; the alloy melting is carried out in an inert atmosphere; the melting is repeated 6 to 8 times, and magnetic stirring is turned on; after the alloy melting is completed, it is cooled by circulating cooling water.
4. The preparation method according to claim 1, characterized in that: In step (2), the temperature of the alloy homogenization is 880-920°C Preferably, the alloy homogenization time is 8 to 10 hours; Preferably, the heating rate of the alloy homogenization is 10-15° C. / min.
5. The preparation method according to claim 1, characterized in that: In step (2), the alloy is further subjected to water cooling and quenching after being homogenized; Preferably, the alloy homogenization is performed in an inert atmosphere.
6. The preparation method according to claim 1, characterized in that: In step (3), the hot rolling process is performed for 8 to 10 passes; the reduction rate of a single pass is 8% to 10%.
7. The preparation method according to claim 6, characterized in that: In the hot rolling process, a heat preservation treatment is also performed before each rolling pass; Preferably, the temperature of the heat preservation treatment is the same as the temperature of the hot rolling treatment; Preferably, in the hot rolling process, the holding time before the first rolling pass is 25 to 35 minutes; the holding time before the remaining rolling passes is 2 to 4 minutes; Preferably, the hot rolling process further includes a water cooling operation.
8. The preparation method according to claim 1, characterized in that: In step (4), the annealing temperature is 650-750° C.; Preferably, the annealing time is 10 to 15 minutes.
9. The preparation method according to claim 1, characterized in that: In step (4), the annealing further includes a cooling operation; Preferably, the cooling is performed by cooling with the furnace to 250-350° C. and then air cooling.
10. The low-alloy high-strength and toughness zirconium alloy obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
High-strength corrosion-resistant weldable aluminum-magnesium-erbium-zirconium alloy wide sheet and preparation method thereof
CN111850361A
High-strength zirconium alloy and preparation method thereof
CN113186425A
Equiaxial high-strength zirconium alloy and preparation method thereof
CN113528894A
Double-state high-strength plastic zirconium alloy and preparation method thereof
CN113549788A
High-strength corrosion-resistant zirconium alloy and preparation method and application thereof
CN113564421A